The regulation of P700 is an important photoprotective mechanism to NaCl-salinity in Jatropha curcas - Cerqueira, João V. A.; Silveira, Joaquim A. G.; Carvalho, Fabrício E. L.; Cunha, Juliana R.; Lima Neto, Milton C. [UNESP] (Wiley, 2019)
Salinity commonly affects photosynthesis and crop production worldwide. Salt stress disrupts the fine balance between photosynthetic electron transport and the Calvin cycle reactions, leading to over-reduction and excess energy within the thylakoids. The excess energy triggers reactive oxygen species (ROS) overproduction that causes photoinhibition in both photosystems (PS) I and II. However, the role of PSI photoinhibition and its physiological mechanisms for photoprotection have not yet been fully elucidated. In the present study, we analyzed the effects of 15 consecutive days of 100 mM NaCl in Jatropha curcas plants, primarily focusing on the photosynthetic electron flow at PSI level. We found that J. curcas plants have important photoprotective mechanisms to cope with the harmful effects of salinity. We show that maintaining P700 in an oxidized state is an important photoprotector mechanism, avoiding ROS burst in J. curcas exposed to salinity. In addition, upon photoinhibition of PSI, the highly reduced electron transport chain triggers a significant increase in H 2 O 2 content which can lead to the production of hydroxyl radical by Mehler reactions in chloroplast, thereby increasing PSI photoinhibition.